The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/13567667211024703
|View full text |Cite
|
Sign up to set email alerts
|

Modeling behavioral intention toward traveling in times of a health-related crisis

Abstract: This study proposes an integrated model based on the Risk Perception Attitude (RPA) framework and the Theory of Planned Behavior (TPB) model to investigate behavioral intention toward traveling in times of a health-related crisis. A survey was conducted via online networks of travelers, yielding 338 valid cases. The findings indicate that health risk perception is affected by information search about the Covid-19 disease. The relationship between health risk perception and behavioral intention toward traveling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 101 publications
1
14
0
Order By: Relevance
“…Golets et al, (2020) study also proved that the health perceived risk has a significant effect on the travel intentions of Brazilians during the COVID-19 outbreak. Other studies confirmed the same results that the health perceived risk has a significant effect on the travel intention during the COVID-19 virus pandemic (Perić et al 2021;Su et al, 2021) The results also showed that there is a positive significant relationship between the perceived travel risk and the intention to travel during the COVID-19 pandemic. These findings are consistent with the study of Angguni, & Lenggogeni, (2021) who found an association between the perceived travel risk and the intention to travel.…”
Section: Discussion Of Resultssupporting
confidence: 70%
“…Golets et al, (2020) study also proved that the health perceived risk has a significant effect on the travel intentions of Brazilians during the COVID-19 outbreak. Other studies confirmed the same results that the health perceived risk has a significant effect on the travel intention during the COVID-19 virus pandemic (Perić et al 2021;Su et al, 2021) The results also showed that there is a positive significant relationship between the perceived travel risk and the intention to travel during the COVID-19 pandemic. These findings are consistent with the study of Angguni, & Lenggogeni, (2021) who found an association between the perceived travel risk and the intention to travel.…”
Section: Discussion Of Resultssupporting
confidence: 70%
“…It is projected that it would take two years to go back to the levels that were before the outbreak [ 140 ]. Numerous scholars have taken an interest in developing and carrying out plans and actions that will bring the travel and tourism sector back to its normal (pre-pandemic) state or to a state that is in some way superior to that normal one [ 142 ]. In this regard, the present study discusses various antecedents and their consequences on revisit intention post-COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the effect of risk perception on travelers intentions is mostly based on the individual psychological level, with insufficient empirical research at the macro level. This study draws on the theoretical basis of research results related to the relationship between risk perception and travelers intentions (Huang et al, 2020; Shin et al, 2022; Su et al, 2022; Zheng et al, 2021), reflecting the basic relationship between the two as defined by risk perception theory (Su et al, 2022). More importantly, this study elevates this psychological relationship to a macropsychological level, exploring the relationship between the two at the regional psychological level, which will enhance the research horizon of risk perception theory and yield new findings at the temporal and spatial dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of such literature is related to risk perception. Several mature frameworks for understanding the impact of risk perception on tourists' intentions have developed, such as health risk model (Huang et al, 2020), motivation protection theory (Zheng et al, 2021), theory of planning behavior (Shin et al, 2022), and risk perception attitude (Su et al, 2022) frameworks. These theories generally suggest that before taking action, people will assess the severity of the epidemic risk and the vulnerability of individuals to threats, and thus form basic judgments about travel decisions (Wang et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%